Gene Expression of Heat Shock Protein (hsp90) Using RT-PCR for Local Isolate of Salmonella - Mohseen, Marwa; AL-Kazazi, Abdul Kareem A; Aziz, Ghazi M (Al-Nahrain Journal of Science, 2018)
Six bacterial isolate were obtained for the genus Salmonella from the central health laboratory ministry of health Baghdad. Then these isolated were identified serologically by antisera test, from statins serum Institut (SSI) using the agglutination reaction (Antigen-antibody complex). The hsp90 gene was identified for the studied isolates by specific primers for gene amplification using PCR technique to include nucleotide sequence up and down stream gene. Results of electrophoresis on agarose gel revealed that the approximate size of the gene is about 161bp.The intensity of gene expression hsp90 for Salmonella Typhimurium measured by CT when the bacterial isolate was exposed to different temperatures (30,40,45,50 and 55) ºC using qRT-PCR result showed a regular increasing of gene expression with temperature, untile a maximum intensity observed at 50 ºC. However the intensity at 55 ºC was statistically insignificant. The impact of UV light at 320nm on gene expression for hsp90 on the Salmonella Typhimurium has been also studied and the results showed significant increase in the gene expression, compared to the normal growth temperature and to the internal positive control(Reference gene) 16sRNA.